2021
DOI: 10.3390/ijms22063023
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles from Mesenchymal Stromal Cells for the Treatment of Inflammation-Related Conditions

Abstract: Over the past two decades, mesenchymal stromal cells (MSCs) have demonstrated great potential in the treatment of inflammation-related conditions. Numerous early stage clinical trials have suggested that this treatment strategy has potential to lead to significant improvements in clinical outcomes. While promising, there remain substantial regulatory hurdles, safety concerns, and logistical issues that need to be addressed before cell-based treatments can have widespread clinical impact. These drawbacks, along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 175 publications
(223 reference statements)
0
34
0
Order By: Relevance
“…However, there are still certain clinical impacts of the direct transplantation of stem cells into target tissues such as tumorigenicity, immune incompatibility, and chromosomal aberrations [ 4 , 5 ]. Because the regeneration, anti-inflammatory, immune regulation, and other functions of stem cells are mainly through their paracrine function [ 6 ], extracellular vesicles (EVs) have been widely studied. As intercellular communication carriers, EVs transfer biologically active lipids, proteins, and nucleic acids including mRNA, microRNA, and long-chain non-coding RNA (lncRNA) between cells, thereby triggering biological responses in recipient cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still certain clinical impacts of the direct transplantation of stem cells into target tissues such as tumorigenicity, immune incompatibility, and chromosomal aberrations [ 4 , 5 ]. Because the regeneration, anti-inflammatory, immune regulation, and other functions of stem cells are mainly through their paracrine function [ 6 ], extracellular vesicles (EVs) have been widely studied. As intercellular communication carriers, EVs transfer biologically active lipids, proteins, and nucleic acids including mRNA, microRNA, and long-chain non-coding RNA (lncRNA) between cells, thereby triggering biological responses in recipient cells.…”
Section: Introductionmentioning
confidence: 99%
“…To sum up, there is growing evidence that, as part of the secretome, the extracellular vesicles (EVs) will be the next effective therapeutic agents deriving from MSCs. Current research concerning MSC-EVs [125,126] as anti-inflammatory [127] and pro-regenerative agents for treating inflammation-related conditions has shown therapeutic potential in preclinical studies as recently reviewed [128]. In most of the cases persistent infections led to increased tissue damage associated with excessive duration of inflammation.…”
Section: Mscs As Source Of Antibiotic-free Nanomaterialsmentioning
confidence: 99%
“…There has been speculation about the role of EVs in mediating cell protection [138] and the host response to infection [128]. Recently, it was also reported that human EVs and exosomes act as cellular decoys and are produced by cells for protection against bacterial pathogens [139,140].…”
Section: Antibacterial Exosomes As Future Biomedicinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the aforementioned bioactive molecules, extracellular vesicles are increasingly being recognized as crucial mediators of MSCs’ biological functions. This concept has been supported by the fact that ΜSC-derived EVs can mimic the biological properties of their parental cells [ 109 ] and can exert similar anti-inflammatory, antiapoptotic, proangiogenic, and immunomodulatory effects in various disease models [ 110 , 111 ]. In the next section, the biology of EVs will be discussed and the immunomodulatory role of MSC-EVs will be explored.…”
Section: Mscs’ Mode Of Actionmentioning
confidence: 99%